Erro de leitura das vogais do inglês americano como língua estrangeira pelos falantes do português do Brasil: das redes de ensino estadual, particular e universidades - Silva Junior, Leônidas José da (2009)
The current research was made in order to demonstrate that students, whose mother language is Brazilian Portuguese (BP), show similar difficulties in learning American English (AE) as a foreign language (EFL). The aim of this research was to investigate the reading process of American English vowels by Brazilian students from Recife/PE, showing reading errors in pronunciation due to a large amount of interferences from their mother language (BP). In here, it was tried to evaluate how social factors such as, age and schooling of mother language which can interfere in the process of the American English acquisition as a foreign language. It was made a percentage process of errors through charts containing number data as well. Identify relations between the AE vowel system and the BP vowel system and how the reading process of EFL is achieved by BP speakers. The research was held in public schools, private schools and universities. For the instrument, it was used phrases containing the twelve vowel sounds of American English. The reading from the speakers works as the methodology of this dissertation. It is concluded that the schooling process displays a deficiency onto the learning of English as a foreign language (EFL). Teachers must be submitted through different training modes and capacitating process so that they can develop a more productive work.